Islamic Animation: Netnographic Analysis on Digital Processing Transformation in Social Media - Hamzah, Hamzah; Ahmad, Shukri; Hamzah, Muhammad Luthfi; Purwati, Astri Ayu; Mutia, Tika (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
A phenomenon that is currently widely discussed is the massive growth of digital creators who are actively sharing unique and popular da'wah concepts, primarily through Islamic animation. The objective of this study is to explore and analyze Islamic animated content on social media and identify the recurring themes found in these contents. The research team collected data by utilizing advanced search features and relevant keywords to locate content that met the specified criteria. Between June 2022 and June 2023, the research team evaluated a total of 5,000 pieces of content sourced from various virtual communities on Indonesia's prominent social media platforms, namely Instagram and YouTube. The first two rounds of evaluation focused on identifying qualitatively significant themes, while rounds 3 to 4 expanded on the initial findings for each social media platform. Employing the Netnography method for analysis, four distinct themes emerged from all Islamic animated content on social media: